Perceptions of the Independence of Judges in Europe Congruence of Society and Judiciary - van Dijk, Frans (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
"In his important book Frans van Dijk changes the usual focus on rules of independence in European countries to the perceptions of independence. This book is a very relevant and timely wake-up call for judges and judicial councils alike. Should be a mandatory read for them all. Highly recommended." - Kees Sterk, Endowed Professor of Administration of European Justice, Maastricht University, the Netherlands, and former President of the European network of Councils for the Judiciary "Frans van Dijk`s book puts the focus on perception of judicial independence. The book is highly recommended and should be mandatory reading for all European judges, particularly in times when judicial independence is challenged in so many European countries." -Wiggo Storhaug Larsen, Appeal Court Judge and President of the Norwegian Judges Association This open access book is about the perception of the independence of the judiciary in Europe. Do citizens and judges see its independence in the same way? Do judges feel that their independence is respected by the users of the courts, by the leadership of the courts and by politicians? Does the population trust the judiciary more than other public institutions, or less? How does independence of the judiciary work at the national level and at the level of the European Union? These interrelated questions are particularly relevant in times when the independence of the judiciary is under political pressure in several countries in the European Union, giving way to illiberal democracy. Revealing surveys among judges, lay judges and lawyers - in addition to regular surveys of the European Commission - provide a wealth of information to answer these questions. While the answers will not please everyone, they are of interest to a wide audience, in particular court leaders, judges, lawyers, politicians and civil servants. Frans van Dijk is Professor of Empirical Analysis of Legal Systems at the Montaigne Centre for Rule of Law and Administration of Justice, Utrecht University, The Netherlands.